Dampak Kualitas Air Tanah Terhadap Kualitas Melon (Cucumis Melo L.) - Setiawati, Rini; Bafdal, Nurpilihan (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2020)
Hydroponic cultivation of melon plants with a fertigation system using ground water is one of the cultivation technologies that is expected to improve the quality and production of crops. Fertigation technology (fertilizer and irrigation) using autopot is an irrigation system allow to provide irrigation water by self-watering system by not using electric power so that the fertigation system is more efficient. The purpose of this study was to determine the effect of the impact of groundwater quality on the quality of melon (Cucumis melo L.) plants. The research method used is descriptive method. The quality parameters of the melon used in this study were water content, carbohydrate, protein, fat, ash, vitamin C and sweetness (% brix). The results of research on ground water quality show that the quality of ground water used is included in the category of non-polluted, which means that the water has good quality. The results showed the quality of melon has an average value of 95.19% fruit water content, 1.99% carbohydrate content, 1.37% protein content, 0.88% fat content, 0.57% ash content, vitamin C 6 , 91%, and total dissolved solids (sweetness) 9.4 0brix. The quality of the melon is classified as low quality according to SNI 7883-2013. The results of the ground water quality and the quality of the melon shows if the ground water affects the quality of the melon plants.